Performance of local West African Shorthorn cattle fed agro-based industrial by products as dry season supplements - Humado, C.K. (1976)
The study was conducted at Agricultural Research Station, University of Ghana, Legon, from December, 1975 to March 1976, to investigate the feeding value of detheobromised roasted cocoa bean shell and ricebran – based diets as dry season supplements for West African shorthorn cattle on the Accra plains. Eighteen West African Shorthorn heifers, of two age groups, (One year old, and two year old) were assigned to a control and two test groups. The control animals were allowed normal grazing, while test group 1 and 2 heifers were fed supplements of detheobromised roasted cocoa bean shell and ricebran – based diets in addition to normal grazing. Supplements were fed at an average of 0.5kg/100 kg bodyweight per animal, each morning, prior to grazing. Average liveweight gain per animal per day over the entire experimental period, for one-year old animals, were 0.05kg, 0.07 kg, 0.07kg for control and test group 1 and 2 animals, respectively. Overall average liveweight gain per animal per day showed no significant differences (p<0.05) suggesting no supplementation effect. However, during late January and early February, when there was a severe dry spell, and crude protein content of pastures fell to about 7.0%, intake of supplements by test group 1 and 2 of animals increased. Except for the ricebran supplemented animals, other groups made slight live weight lesses during this period. Overall results of this experiment suggest a possible advantage in supplementation with detheobromised roasted cocoa bean shell and rice bran based diets, during a severe dry season period.